Pengaruh Lokasi, Harga dan Label Halal Terhadap Keputusan Pembelian Pada Produk Wardah di Toko Aster Malang - Sita Agustin; Candra Wahyu Hidayat; Rusno Rusno (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2018)
This study aims to determine the effect of Location, Price and Halal Labels on Purchasing Decisions of Wardah Products in Malang. This type of research is quantitative research. The population in this study were consumers in Malang who bought Wardah products with a sample size of 112 respondents. The data collection technique used was a questionnaire. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that the location, price and halal variables partially have a positive effect on the purchasing decision of Wardah products in Malang Aster Shop. As well as location, price and halal labels simultaneously have a positive effect on the decision to purchase Wardah products in Aster Store Malang.